Frozen Embryo Transfer in Mildly Stimulated Cycle With Letrozole Compared to Natural Cycle in Ovulatory Women: A Large Retrospective Study - Li, Danjun; Khor, Shuzin; Huang, Jialyu; Chen, Qiuju; Lyu, Qifeng; Cai, Renfei; Kuang, Yanping; Lu, Xuefeng (Frontiers in Endocrinology, 2021)
Abstract Objective: To evaluate the clinical effect of mild stimulation with letrozole on pregnancy outcomes in ovulatory women undergoing frozen embryo transfer (FET) compared to natural cycle. Design: Retrospective observational study. Setting: Tertiary care academic medical center. Population: A total of 6,874 infertile women with regular menstrual cycles (21-35 days) met the criteria for this study in the period from 2013 to 2020. Methods: All patients who were prepared for and underwent FET were divided into two groups: a modified natural cycle (NC) group (n=3,958) and a letrozole cycle group (n=2,916). Main outcome measures: The primary outcome of the study was clinical pregnancy rate. Secondary outcome measures were endometrial thickness, rates of implantation, positive HCG test, live birth, early miscarriage and ectopic pregnancy. Results: The clinical pregnancy rate was not statistically different between the modified NC-FET group and the letrozole-FFT group before (crude OR 0.99, 95% CI 0.90-1.09, P=0.902>0.05) and after propensity score matching (PSM) (crude OR 1.01, 95% CI 0.91-1.12, P=0.870>0.05). After multivariable logistic regression analysis, the clinical pregnancy rate remained insignificant before (adjusted OR 1.00, 95% CI 0.91-1.10, P=0.979>0.05) and after matching (adjusted OR 1.00, 95% CI 0.89-1.11, P=0.936>0.05), respectively. Similarly, in the crude and adjusted analysis, the positive HCG test, implantation, live birth and early miscarriage rates were also comparable in the letrozole-FFT group and modified NC-FET group before and after matching. Furthermore, the endometrial thickness of letrozole-FFT group was similar to that of modified NC-FET group with adjusted analysis. Conclusion: Our observation suggests that mild stimulation with letrozole could produce similar pregnancy outcomes in ovulatory patients who undergo FET when compared with a natural cycle.